PENDAMPINGAN KEGIATAN OLIMPIADE SISWA NASIONAL BIDANG KOMPUTER PADA SISWA SMA NEGERI 1 PRAMBANAN SLEMAN - Muhammad Sholeh; Dina Andayati; Suraya Suraya (ABDI MAKARTI, 2023)
The National Student Olympiad (OSN) is an academic competition held annually by the Indonesian Ministry of Education and Culture for high school students. As one of the public schools in Sleman, SMA Negeri 1 Prambanan always sends students to the OSN. Preparatory efforts are always made so that students can be maximised in participating in the OSN. The OSN mentoring activity for the SMA Negeri 1 Prambanan team in 2023, especially in the computer field, was held at the AKPRIND Institute of Science & Technology computer laboratory. This activity aims to make students have an overview of OSN questions and the process of solving answers, especially programming questions. By discussing OSN material, the expected benefits include, among others, increasing student learning motivation. By understanding the types of questions and the process of solving them, students can feel more prepared and motivated to take part in the OSN. The mentoring was carried out with a training method by explaining the material and discussing OSN questions in 2022. The training material provided starts from basic computer theory, programming logic to programming material using the C++ language.  The results of the activity, students have an overview of OSN questions and the process of solving answers, especially programming questions.  Students' understanding, especially programming questions, increased and students' understanding of OSN questions and the process of solving answers, especially programming questions, can provide positive benefits for learning abilities and student achievement.